TENSIONS POSSIBLY APPEARING BETWEEN BELIEFS OF SYLLABUS DEVELOPERS (Eurasian Journal of Philology Science and Education, 2018)
The author generalizes some data from the secondary research of world well-known syllabus designers as well as some information from his own teaching experience, then, suggests some recommendation on solving the dilemmas and difficulties which occur during culture related syllabus designing process. Thus, the article examines the importance of teachers’ sociocultural beliefs and values and how they influence the development of a course. In the sphere of world higher education, it is noticed that there are different cultural values between teachers and students, as well as different values between teachers. It also looks into why there are sometimes discrepancies between the beliefs of teachers of the same profession, even the same teaching experience and almost the same age. This work examines what types of tension there can be, why they can exist and how they can be overcome. The focus of this paper is on the differences in the values and beliefs between teachers as course developers who are experienced in curriculum and syllabus developing for courses, mainly in the area of studying culture in the field of education.